Delamination of southern Puna lithosphere revealed by body wave attenuation tomography. Issue 1 (28th January 2014) - Liang, Xiaofeng; Sandvol, Eric; Kay, Suzanne; Heit, Benjamin; Yuan, Xiaohui; Mulcahy, Patrick; Chen, Chen; Brown, Larry; Comte, Diana; Alvarado, Patricia
Abstract The southern Puna Plateau has been proposed to result from a major Pliocene delamination event that has previously been inferred from geochemical, geological, and some preliminary geophysical data. Seventy‐five seismic stations were deployed across the southern Puna Plateau in 2007–2009 by scientists from the U.S., Germany, Chile, and Argentina to test the delamination model for the region. The Puna passive seismic stations were located between 25 and 28°S. Using the seismic waveform data collected from the PUNA experiment, we employ attenuation tomography methods to resolve both compressional and shear quality factors (Qp and Qs, respectively) in the crust and uppermost mantle. The images clearly show a high‐Q Nazca slab subducting eastward beneath the Puna plateau and another high‐Q block with a westward dip beneath the Eastern Cordillera. We suggest that the latter is a piece of delaminated South American lithosphere. A significant low‐Q zone lies between the Nazca slab and the South American lithosphere and extends southward from the northern margin of the seismic array at 25°S before vanishing around 27.5°S. This low‐Q zone extends farther west in the crust and uppermost mantle at the southern end of the seismic array. The low‐Q zone reaches 100 km depth beneath the northern part of the array but only 50 km depth in the south. Lateral variations of the low‐Q zone reflect the possible mechanism conversion between mantle upwelling related to delamination and dehydration. The depth of the Nazca slab as defined by Q images decreases from north to south beneath the plateau, which is consistent with the steep‐flat transition of the angle of the subducting slab as defined by previous earthquake studies.